2019
DOI: 10.1371/journal.pone.0215088
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of microRNA-4474/4717 expression and CREB-binding protein in human colorectal cancer tissues infected with Fusobacterium nucleatum

Abstract: Colorectal cancer (CRC) is a common and highly lethal form of cancer. Although the etiologic role of Fusobacterium nucleatum ( F . nucleatum ) in the development of CRC has been elucidated, the specific tumor molecules involved in the progression of CRC induced by F . nucleatum have not been identified. This study investigated several miRNAs and genes involved in the progression of F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…PRKACB mutations and gene fusion of PRKACB can lead to adrenal, bile duct, liver, and pancreatic cancers [12,13], meanwhile down-regulation of PRKACB expression may be associated with poor survival in patients with non-small cell lung cancer. Makondi et al found that targeting PRKACB may increase the responsiveness of colorectal tumors to irinotecan treatment [28], and Feng et al also found pathological expressions of PRKACB in human colorectal cancer tissues infected with nucleobacteria [29]. Consistent with previous studies [30], our study showed that PRKACB had a significant discrepancy of expression in normal and tumor tissues of colorectal cancer, and we also depicted that down-regulation of PRKACB expression is a risk factor for declining 1, 3, and 5-year survival rates in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRKACB mutations and gene fusion of PRKACB can lead to adrenal, bile duct, liver, and pancreatic cancers [12,13], meanwhile down-regulation of PRKACB expression may be associated with poor survival in patients with non-small cell lung cancer. Makondi et al found that targeting PRKACB may increase the responsiveness of colorectal tumors to irinotecan treatment [28], and Feng et al also found pathological expressions of PRKACB in human colorectal cancer tissues infected with nucleobacteria [29]. Consistent with previous studies [30], our study showed that PRKACB had a significant discrepancy of expression in normal and tumor tissues of colorectal cancer, and we also depicted that down-regulation of PRKACB expression is a risk factor for declining 1, 3, and 5-year survival rates in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that microRNAs can regulate the expression of PRKACB [29,[36][37][38], affect cell proliferation, adhesion, and metastasis, and eventually bring about the development of tumors. Also, studies have found that antisense oligodeoxynucleotides targeted to protein kinase subunits induce growth arrest, apoptosis, and differentiation in a variety of cancer cell lines both in vitro and in vivo [39].…”
Section: Discussionmentioning
confidence: 99%
“…Based on an integrative meta-analysis, CAMK2B was found to be associated with the development of cancer cachexia [56]. Recently, Feng et al [57] assayed 15 colorectal cancer tissues and 10 paracancerous tissues using microarrays and found that CAMK2B was involved in the progression of Fusobacterium nucleatum-induced colorectal cancer. Another study also reported that CAMK2B played an important role in glioblastoma multiforme using bioinformatics analysis on publicly available datasets [58].…”
Section: Discussionmentioning
confidence: 99%
“…We used online prediction software CircBank, Targetscan, and miRWalk, which resulted in the identification of 6 miRNAs (miR-7-1-3p, miR-1290, miR-219b-3p, miR-4736, miR-6808-5p, and miR-6893-5p) that might be targeted by circ_0060745 ( Figure 3C). Analysis of the GEO dataset GSE122182 24 resulted in the selection of miR-4736 (probe ID: hsa-miR-4736_st) for further study, as the expression of this microRNA was downregulated in 15 CRC samples compared to that in 10 paratumor samples ( Figure 3D and E). Upregulation of miR-4736 suppressed proliferation and metastasis of LOVO and HT29 cells ( Figure 3F and G), and vice versa ( Figure 3H).…”
Section: Microrna 4736 Acted As a Tumor Suppressor In Ht29 And Lovo Cmentioning
confidence: 99%